Ocorrência de Listeria spp. e de Listeria monocytogenes, em um matadouro-frigorífico de bovinos do estado de São Paulo - Caselani, Kelly [UNESP]; Prata, Luiz Francisco [UNESP]; Bizari, Paula Adriana [UNESP]; Pereira, Gener Tadeu [UNESP]; de Marchi, Patrícia Gelli Feres [UNESP]; Picinato, Mirelle Andréa de Carvalho [UNESP] (My University, 2013)
We evaluated the presence of Listeria spp. and Listeria monocytogenes in environmental samples by means of swabs collected the bovine slaughter plant enabled to export, located in the state of Sao Paulo, Brazil. After the pre-enrichment at 30±1°C for 22 to 26h the samples were analyzed using the BAX System Listeria. Those positive for Listeria spp. were submitted a second PCR reaction to confirm the presence of Listeria monocytogenes. From 411 environmental samples analyzed, 62 (15.1%) were positive for Listeria spp. and 21 (5.1%) for Listeria monocytogenes, which showed their persistence in the slaughter plant. There were no statistical differences between the rainy and dry periods and between areas sampled, although it has been found between sectors. The floor surface and the sector cuts have higher rates of positivity.

A ocorrência de Listeria spp. e de Listeria monocytogenes, foi avaliada em amostras ambientais por meio de suabes colhidos em matadouro-frigorífico de bovinos habilitado à exportação, localizado no Estado de São Paulo, Brasil. Após o pré-enriquecimento a 30 ± 1oC por 22 à 26h as amostras foram analisadas empregando o BAX® System Listeria. As amostras positivas para Listeria spp. foram submetidas à uma nova reação de PCR para a confirmação da presença de Listeria monocytogenes. Das 411 amostras ambientais analisadas, 62 (15,1%) foram positivas para Listeria spp. e 21 (5,1%) para Listeria monocytogenes (5,1%), o que mostrou sua persistência na planta de abate. Não foi detectada diferença estatística entre os períodos seco e chuvoso e entre as superfícies amostradas, porém diferença estatística foi encontrada entre setores. A superfície do piso e o setor de cortes apresentaram os maiores índices de positividade.
Occurrence of Listeria spp.and Listeria monocytogenes, at a slaughterhouse bovine of the state of São Paulo
Keywords: Bovine; Listeria spp; Polymerase chain reaction (PCR); Slaughter